Nonlinear Hall effects in strained twisted bilayer WSe2 - Jin-Xin Hu; Cheng-Ping Zhang; Ying-Ming Xie; K. T. Law (Communications Physics, 2022)
The nonlinear Hall effect describes a recently discovered phenomenon in which a time-reversal symmetric material with a Berry curvature dipole develops a transverse voltage at double the frequency of an applied current. Here, the authors theoretically explore twisted bilayer WSe2 under strain, and find that it can exhibit a large nonlinear Hall effect that is highly sensitive to the topological properties of the material.